House price booms, current account deficits, and low interest rates - Andrea Ferrero (Federal Reserve Bank of New York, 2012)
One of the most striking features of the period before the Great Recession is the strong positive correlation between house price appreciation and current account deficits, not only in the United States but also in other countries that have subsequently experienced the highest degree of financial turmoil. A progressive relaxation of credit standards can rationalize this empirical observation. Lower collateral requirements facilitate access to external funding and drive up house prices. The current account turns negative because households borrow from the rest of the world. At the same time, however, the world real interest rate counterfactually increases. The two key ingredients that reconcile a demand-based explanation of house price booms and current account deficits with the evidence on real interest rates are nominal interest rates lower than the predictions of a standard monetary policy rule in leveraged economies and foreign exchange rate pegs in saving countries.
Keywords: E43; E52; E58; F32; F41; 330; borrowing constraints; monetary policy shocks; exchange rate pegs